2010
DOI: 10.1007/s00384-010-0878-9
|View full text |Cite
|
Sign up to set email alerts
|

An endoscopic training model to improve accuracy of colonic polyp size measurement

Abstract: This training model could help endoscopists improve the accuracy of measurement of polyps on colonoscopy in a short period. The durability of learning effect needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A previous study at a single center also verified the usefulness of an educational module with video clips of polyp size estimations with and without a flexible measuring probe 12. However, interest in polyp size estimation, which may influence the motivation of the participants to learn, may already be higher in that institution owing to the presence of specialists who may have emphasized on the need for accurate polyp size estimation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A previous study at a single center also verified the usefulness of an educational module with video clips of polyp size estimations with and without a flexible measuring probe 12. However, interest in polyp size estimation, which may influence the motivation of the participants to learn, may already be higher in that institution owing to the presence of specialists who may have emphasized on the need for accurate polyp size estimation.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that beginner endoscopists are less accurate in the visual estimation of polyp size than expert endoscopists 12,13. As even the size estimation by experts who educate beginners is inaccurate,4,5,6,14 an educational tool that allows accurate visual estimation of polyp size without relying on endoscopic equipment is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that repeated polyp size measurement using tools is helpful in training for accurate visual measurements [ 24 , 25 ]. Therefore, we believe that the gCAP method may be useful in the training of beginner endoscopists for improved VE ability.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Chi Yang et al. [28] also found that the interobserver inconsistency in polyp size measurements and the difference in diagnostic classification by pathologists led to spurious differences in estimates of the prevalence of advanced adenomas.…”
Section: Discussionmentioning
confidence: 99%